2018
DOI: 10.21859/ijnr-13015
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Emotional stability with Job conscience and professional commitment

Abstract: Introduction: Emotional stability is a personality trait that includes natural and constant domains of emotions found in individuals at different stages of life and in different environments.This study aimed at determining the relationship of emotional stability with job conscience and professional commitment. Methods: This study had a descriptive-analytical design. This study was conducted on 200 nurses of Kerman University of Medical Sciences through cluster random sampling. Data was gathered using a questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…In addition, professional commitment scores were classified as high (scores 45 and more), medium (scores 30-45), and low (scores 30 and less). The study of Hosseini and Soltani in Iran showed that this questionnaire has a high face and content validity [25]. The reliability of this tool was also confirmed by the Cronbach alpha coefficient of 90% for the present study.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, professional commitment scores were classified as high (scores 45 and more), medium (scores 30-45), and low (scores 30 and less). The study of Hosseini and Soltani in Iran showed that this questionnaire has a high face and content validity [25]. The reliability of this tool was also confirmed by the Cronbach alpha coefficient of 90% for the present study.…”
Section: Methodssupporting
confidence: 76%
“…The results of the present study showed that the nurses under study have a high professional commitment, which is consistent with the results of the Nogueras study [28], which could be due to the conditions prevailing in the workplace. In the study of Hosseini and Soltani, which was performed using the tools used to investigate professional commitment in this study, many nurses had a high level of professional commitment, with which the results of the present study are similar [25].…”
Section: Discussionsupporting
confidence: 67%
“…This collaboration is imperative for ensuring the efficacy of surgeries. The results of a study by Hosseini et al demonstrated a positive and direct statistical relationship between teamwork and job motivation, indicating that higher job motivation correlates with improved teamwork ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the nurses' most important professional tasks is to provide care and implement nursing interventions (8). Therefore, it can be said that the basis of nursing is to create a suitable care environment for patient recovery (9).…”
Section: Introductionmentioning
confidence: 99%